Towards Distributed Interaction Systems in theVirtuality Continuum - Gerald Melles (2019)
This thesis explores a range of interaction objects in terms of the requirements their integration into a virtuality continuum (VC) application would pose, based on experiments and feasibility studies in the Creative Space for Technical Innovations and elsewhere. It thereby acts as a starting point for the development of comprehensive solutions for the integration of distributed interaction systems, as well as a basis for their evaluation.